The Influence of Sufi-Centric Movements on the Flourishing of Islamic Plurality in the Indian Subcontinent - Chowdury, Saeyd Rashed Hasan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This article explores the multi-faceted impact of Sufi ideological groups such as Deobandi, Tablighi Jamaat, Darul Uloom Nadwatul Ulama Nadwi, and Barelvi movements on the dissemination of Islam in the Indian subcontinent. It focuses on the educational contributions of Sufi institutions, particularly Khanqahs and Madrasahs, which were pivotal in spreading Islamic knowledge, including theology, literature, arts, and sciences. The study provides a historical overview of Sufism’s evolution in the region and analyses the distinct methods of Islamic propagation used by these four movements. Methodologically, the research employs historical analysis, primary source examination, and socio-cultural investigation to uncover how Sufi scholars facilitated spiritual enlightenment, fostering acceptance of Islam across diverse communities. Findings reveal that while Deobandi and Nadvi groups propagated Islam through madrasas, Tablighi Jamaat utilized mosques and outreach to non-Muslims, and Barelvi groups focused on Khanqahs. The study highlights the Sufi movements’ role in promoting communal harmony, religious tolerance, and peaceful coexistence. The research offers original insights into the socio-cultural influence of Sufi teachings in shaping Islam’s spread and calls for further investigation into their contemporary impact on interfaith relations in the region. Recommendations include strengthening Sufi educational institutions to foster peace and tolerance.